Legal position of management in Republic of Slovenia - Senčur Peček, Darja (Anali PAZU, 2022)
The author deals with definiton of notion of management (managerial staff), discusses a present legal regulation of employment position of management in Republic of Slovenia and their participation in management. The author exposes some imperfections of present legal regulation and proposes possible solutions.